Argentophilicity-dependent colossal thermal expansion in extended prussian blue analogues. - Goodwin, A; Keen, D; Tucker, MG; Dove, M; Peters, L; Evans, J (2008)
The thermal expansion behavior of isostructural variants of the colossal thermal expansion material Ag3[CoIII(CN)6] has been investigated using variable temperature X-ray and neutron powder diffraction. It was found that substitution at the octahedral transition metal site did not strongly affect the thermal expansion behavior, giving Ag3[FeIII(CN)6] as a new colossal thermal expansion material. Substitution at the Ag site (by D) was shown to reduce the thermal expansion coefficients by an order of magnitude. It was proposed that this correlation between the presence of argentophilic interactions and extreme thermal expansion behavior may explain a variety of thermal effects in flexible framework materials containing metallophilic interactions.